Aktywność cyfrowa seniorów i jej znaczenie dla partycypacji osób starszych w życiu online na platformach społecznościowych - Sikorska, Joanna (Pedagogika Społeczna Nova, 2024)
Internet use is no longer reserved exclusively for young people. In recent years, an increasing number of seniors have started using it, and they currently constitute a significant group of users, as shown, among other things, by the results of the 2019 Polish survey conducted by the senior citizens portal https://cafesenior.pl/. While the analyses indicate that email and search engines are still the most important internet functions for this group of people, one can also see a marked increase in seniors’ interest in social media platforms. Although this trend has been going on around the world since 2010, in contrast to many European countries, where indicators reach over 80% among people 60+, in Poland only one-fifth of older people have actively participated in social media. The article has the character of a contributory socio-pedagogical sketch on socially important issues related to the e-inclusion of seniors in cyberspace and its determinants, areas of participation of people aged 60+ in social media and selected stimulators and inhibitors of their digital participation in online social life.